Computational and experimental insights into the spectroscopy, electronic states, and molecular docking of (2S)-2,6-diaminohexanoic acid [DAHA] - T. Amna Sherin; P. V. Abdul Nazar; Sandhya Savita; Mudassar Shahid; Nazia Siddiqui; Saleem Javed (BMC Chemistry)
Abstract This paper presents a theoretical analysis of the l-Lysine molecule using the DFT (density functional theory) method with a 6-311+ + G(d,p) basis set, a quantum–mechanical atomistic simulation method. The research encompasses the analysis of optimized chemical structure, vibrations, FMO, ELF, NLO, RDG, etc., to study the molecule's intensive properties, stability, and other biological activities. IR and UV spectra were analysed for the spectrochemical study, and the VEDA program was used to determine the PED values. The chemical reactivity of the molecule was identified through analysis of the Frontier molecular orbitals, Fukui, and molecular electrostatic potential. The electron localization function and reduced density gradient were determined to understand bonding and electronic structure. The temperature dependence on the properties of the molecule was estimated. The optical properties of the molecule were discussed by analyzing the non-linear optical property. The feasibility of the molecule as a therapeutic drug was examined using the drug likeness concept. Molecular docking analysis was conducted to acquire the best ligand–receptor complex and to study the molecule's biological activity.